Status and associates of knowledge, attitude, and practice about individual dining system among residents in Wuhan municipality: a community-based online survey - Xin MEI; Jin FENG; Man CHEN; Yuan-xia HUYANG (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo examine the status and influencing factors of knowledge, attitude, and practice (KAP) about individual dining system among 15 - 69 years old residents in Wuhan municipality and to provide a reference for formulating targeted health education on individual dining system. MethodsWith stratified multistage random sampling and Questionnaire Star Application, an online self-administered survey was conducted on KAP about individual dining system among 3 600 permanent residents aged 15 - 69 years in 70 urban communities/rural villages of Wuhan municipality, Hubei province during December 2020. ResultsOf the 3347 participants finally included in the analysis, 2087 (62.35%), 2883 (86.14%) and 1825 (54.53%) were assessed as having qualified KAP about individual dining system, respectively. The results of unconditional multivariate logistic regression analysis indicated that the participants with following characteristics were more likely to have a qualified KAP about individual dining system: (1) being female for qualified KAP; (2) being a civil servant for qualified knowledge and attitude; (3) being a teacher or with an education of master degree and above for qualified attitude; (4) aged 35 years and older for qualified practice. ConclusionAmong the 15 - 69 years old residents in Wuhan city, the proportion of having a more positive attitude towards the individual dining system is high but that being aware of relevant knowledge and taking right actions are relatively low, and gender is a common factor influencing the KAP about individual dining system.